Synthesis and mechanical characterisation of self-lubricating Al7075/MoS2/ZrB2 hybrid composite - Dubey M.; Kumar N.; Mohan S. (My University, 2025)
In the current study, Al7075-based hybrid composites reinforced with zirconium diboride (ZrB2) and molybdenum disulphide (MoS2) particles were synthesised through a two-step stir casting process. Three distinct compositions Al7075 alloy, Al7075 + 3 vol.%MoS2 and Al7075 + 3 vol.%MoS2 + 3 vol.%ZrB2 have synthesised using the stir casting process. X-ray diffraction (XRD), optical microscopy, scanning electron microscopy (SEM) along with energy dispersive spectroscopy (EDS), transmission electron microscopy (TEM), and mechanical characterisation were performed on all synthesised samples to identify reinforcement particles, grain refinement, particle morphology, hardness, tensile properties and failure mode. Microstructural examination reveals refined grain structure, uniform distribution of particles, along with clear interface and good bonding. Mechanical characterisation reveals Al7075/MoS2/ZrB2 hybrid composite with highest hardness, strength, and ductility among all the compositions examined. Increased strength along with good ductility of composite over the unreinforced alloy is an important finding of the present study in contrast with many previous studies. Microstructure and mechanical features were correlated with results obtained for enhanced performance and life span of the hybrid composites. Copyright © 2023 Inderscience Enterprises Ltd.